The Effect of pH towards Copper (II) Bromide Reaction in Surfactant Determination - Tan, Jing June; Hashim, NOR HASLINA BINTI HASHIM (Progress in Engineering Application and Technology, 2025)
This study explores the interaction between copper (II) bromide (CuBr2), triethylamine (TEA), and sodium dodecyl sulfate (SDS) to enhance the detection of anionic surfactants in aqueous environments. Anionic surfactants, widely present in household, agricultural, and industrial products, contribute significantly to environmental pollution due to their persistence and potential toxicity. Traditional detection methods, such as the Methylene Blue Active Substances (MBAS) technique, rely on hazardous solvents like chloroform and are labour-intensive, posing environmental and health risks. This research proposes a novel spectrophotometric approach utilizing CuBr2 as an ion-pairing agent, eliminating the need for toxic solvents while improving accuracy and efficiency and focusing on determining the effect of pH on the interaction between SDS and CuBr2. Solutions were prepared with varying concentrations of SDS (0.05 mM to 0.5 mM) and adjusted to pH levels of 4, 6, and 10 using hydrochloric acid and sodium hydroxide. A calibration curve was constructed at a wavelength of 650 nm to demonstrate the linear relationship between SDS concentration and absorbance, adhering to Beer-Lambert’s law. The R2 of 0.936 was obtained as well as the linear equation, y = 0.1111x+0.0575. Results revealed that pH significantly influences the reaction dynamics, with pH 6 identified as the optimal range for efficient ion-pairing and the formation of surfactant-metal complexes. The study provides an effective method for quantifying surfactants in synthetic water samples, enhancing environmental monitoring capabilities while minimizing chemical hazards. This research paves the way for further advancements in water quality assessment and pollutant control.